Phytochemical analysis, antiproliferative and apoptosis-inducing properties of Persicaria strigosa Nakai - Ananta Swargiary, Mritunjoy Kumar Roy, Harmonjit Boro, Akalesh Kumar Verma, Manita Daimari, Jayanta Kumar Das (Journal of Applied Pharmaceutical Science, 2023)
Persicaria strigosa is an important medicinal plant having several ethnomedicinal values. This study investigated the phytochemical contents, antiproliferative, and apoptosis-inducing properties of P. strigosa. The phytocompounds were identified by the Gas Chromatography-Mass Spectrometry (GC-MS) technique. Antiproliferative and apoptosis-inducing properties were conducted in Dalton’s lymphoma cells. In-silico molecular docking, drug-likeness, absorption, distribution, metabolism, excretion, and toxicity (ADMET) were carried out to study the binding affinity and drug-likeness of the compounds. The study revealed a dose-dependent antiproliferative activity of the plant. GC-MS study identified 12 compounds from the ethyl acetate extract. Phytompounds C2, C5, C6, C7, and C12 showed the best binding affinity with the anti-apoptotic proteins. The phytocompounds were predicted to possess drug-likeness properties and a good ADMET profile. The findings suggest that P. strigosa could be a potential source of anticancer agents.